SCIENTIFIC MIRACLES IN MODERN ISLAMIC THEOLOGY-A CRITICAL ANALYTICAL STUDY IN LIGHT OF CONTEMPORARY EPISTEMOLOGICAL APPROACHES - Dr. Sadiq Kazem Mukallaf (Sciental Journals Publishing, 2026)
The matter of scientific miracles is a significant challenge in current Islamic theology, as it reevaluates the connection between religious scriptures and contemporary cosmic findings. This new theological approach seeks to move beyond superficial readings that directly link every scientific phenomenon to a Quranic verse, offering instead a critical methodology that balances the sanctity of the text with the limitations of empirical sciences. A number of contemporary researchers believe that the concept of scientific miracles, as presented in some religious discourses, burdens the text with interpretations it cannot bear, subjecting divine revelation to the whims of evolving theories.
Keywords: Scientific miracle, new theology, Rhetoric of the miracle, Cognitive miracle, Cosmological vision in Islam, Critique of the scientific miracle.